Minimalism - Meyer, James Sampson, 1962- (London ; New York : Phaidon, 2005)
The term, Minimalism, was coined to describe the work of a group of American artists who developed a new kind of whole or serial geometric abstraction during the 1960s. This book documents the careers of the leading figures associated with Minimalism--Carl Andre, Dan Flavin, Donald Judd, Sol LeWitt and Robert Morris--as well as the practices of artists who were associated with the movement, among them the sculptors, Larry Bell, Eva Hesse, John McCracken, Robert Smithson and Anne Truitt; and the painters, Jo Baer, Robert Mangold, Brice Marden, Agnes Martin, David Novros, Robert Ryman and Frank Stella
Preface / James Meyer -- Survey / James Meyer -- Works. 1959-63 First Encounters. 1964-67 High Minimalism. 1967-79 Canonization/Critique. 1980-present Recent Work -- Documents. 1959-63 First Encounters. 1964-67 High Minimalism. 1967-79 Canonization/Critique. 1980-present Recent Writings
Includes bibliographical references (pages 296-298) and index.
Keywords: Minimal art